E-Cigarettes and Cardiopulmonary Health: Review for Clinicians. Issue 3 (18th January 2022) - Neczypor, Evan W.; Mears, Matthew J.; Ghosh, Arunava; Sassano, M. Flori; Gumina, Richard J.; Wold, Loren E.; Tarran, Robert
Abstract : Electronic cigarettes (e-cigarettes) are battery powered electronic nicotine delivery systems that use a propylene glycol/vegetable glycerin base to deliver vaporized nicotine and flavorings to the body. E-cigarettes became commercially available without evidence regarding their risks, long-term safety, or utility in smoking cessation. Recent clinical trials suggest that e-cigarette use with counseling may be effective in reducing cigarette use but not nicotine dependence. However, meta-analyses of observational studies demonstrate that e-cigarette use is not associated with smoking cessation. Cardiovascular studies reported sympathetic activation, vascular stiffening, and endothelial dysfunction, which are associated with adverse cardiovascular events. The majority of pulmonary clinical trials in e-cigarette users included standard spirometry as the primary outcome measure, reporting no change in lung function. However, studies reported increased biomarkers of pulmonary disease in e-cigarette users. These studies were conducted in adults, but >30% of high school–age adolescents reported e-cigarette use. The effects of e-cigarette use on cardiopulmonary endpoints in adolescents and young adults remain unstudied. Because of adverse clinical findings and associations between e-cigarette use and increased incidence of respiratory diseases in people who have never smoked, large longitudinal studies are needed to understand the risk profile of e-cigarettes. Consistent with the Centers for Disease Control and Prevention recommendations, clinicians should monitor the health risks of e-cigarette use, discourage nonsmokers and adolescents from using e-cigarettes, and discourage smokers from engaging in dual use without cigarette reduction or cessation. Abstract : Supplemental Digital Content is available in the text.